EXPLORE THE CHARACTER OF SOIL SPECTRAL REFLECTANCE RELATE TO THE SOIL ORGANIC MATTER CONTENT - Sari Virgawati; Muhjidin Mawardi; Lilik Sutiarso; Sakae Shibusawa; Hendrik Segah; Masakazu Kodaira (The University of Lampung, 2019)
ABSTRACTThe visible and near-infrared (Vis-NIR) diffuse reflectance spectroscopy has emerged as a rapid and low-cost tool for extensive investigation of soil properties. The objective of this research was to explore how significant the relationship between the soil spectral reflectance and soil organic matter (SOM) content. Some soil samples in Yogyakarta were taken for SOM content and spectroscopy measurement. The SOM was analyzed using Walkley and Black method, while the spectral reflectance was determined using ASD Field-spectrophotometer by scanned the sample with Vis-NIR spectrum. Pearson’s coefficient showed that there was a strong negative correlation between SOM and soil spectral of certain wavelengths. Soil with less organic matter content performed high reflectance. Keywords: Soil organic matter; Vis-NIR spectroscopy; soil reflectance; Pearson’s correlation coefficient.